CROPPING OTOMATIS PADA NASKAH BRAILLE - Michiko Ang; Chairisni Lubis (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Braille characters are characters that are used by blind persons to write and read by touching the raised dots that exist on these characters. With the use of automatic cropping process with histogram to get one cell and one single dot for the preprocessing process, this will help to get the braille cell and one single dot easily for the further recognition. The average value of automatic cropping for braille texts reached 98,16%. Key Words automatic cropping, naskah braille